Effectiveness and mechanism of moxibustion in treating chronic non-specific low back pain: study protocol for a multicenter randomized controlled trial - Wang, Xuewei; Zhu, Caifeng; Pan, Hongping; Liang, Dongsheng; Zhao, Nana; Wang, Mingming; Zhou, Bingyuan; Xiang, Han (Frontiers in Medicine, 2025)
IntroductionChronic non-specific low back pain (CNLBP) represents the most commonly encountered subtype of low back pain (LBP) in clinical practice. It has no clearly identified etiological factors and is prone to recurrence, which severely compromises patients’ quality of life. Moxibustion therapy is commonly utilized in China for managing chronic pain conditions and has demonstrated favorable clinical outcomes. However, high-quality randomized controlled trials remain scarce, and the mechanism of action of moxibustion remains unclear. This severely restricts the credibility of moxibustion therapy and its global promotion and application. Consequently, the present research aims to conduct a comprehensive evaluation of the therapeutic efficacy of moxibustion for the management of CNLBP. Additionally, this study will employ modern scientific techniques to conduct a preliminary investigation into the mechanism of action of moxibustion.Methods and analysisThis study will be conducted simultaneously across three tertiary hospitals in China. 150 participants diagnosed with CNLBP will be recruited for this study. Subsequently, these participants will be randomly assigned, following a 1:1 allocation ratio, to undergo either moxibustion or sham moxibustion intervention in accordance with the established research protocol. Treatment will be administered at an identical set of acupoints for all participants: bilateral BL23 (Shenshu), GV3 (Yaoyangguan), and GV8 (Jinsuo). Each session will last 30 min, administered three times weekly for 8 weeks, and an 8-week follow-up will be conducted after the completion of the moxibustion intervention. Change in Numerical Rating Scale (NRS) scores from baseline to the 8-week post-intervention assessment constitutes the primary outcome measure. Secondary outcomes will include assessments via the Oswestry Disability Index (ODI), Fear-Avoidance Beliefs Questionnaire (FABQ), 36-Item Short Form Health Survey (SF-36), Global Perceived Effect (GPE), and functional near-infrared spectroscopy (fNIRS). Evaluations for this research will be conducted at baseline, following the intervention (the fourth week), after the completion of intervention (the eighth week), and during the follow-up period (week 16).DiscussionThe results obtained from this research are expected to indicate that moxibustion therapy can function as a highly efficacious treatment approach for managing CNLBP. Additionally, this trial will employ fNIRS technology to investigate the activation characteristics of pain-related cortical regions in the brains of CNLBP patients before and after moxibustion treatment. This will contribute to elucidating the underlying mechanisms of moxibustion.